KIAT NABI MUHAMMAD SALLALLAHU ‘ALAIHI WA SALLAMMENGURAI KRISIS EKONOMI - Muhamad Arifin (Al-Majaalis : Jurnal Dirasat Islamiyah, 2020)
The world, without exception, our country, is being hit by the Covid-19 outbreak, which until now is not clear when it will end. This epidemic is not only threatening public health, but also collapses all aspects of the world economy. From the scale of the country, corporations, SMEs, to individuals, are affected by this outbreak.Not surprisingly, all circles are struggling to find a way to survive these two great threats; the covid-19 outbreak and the economic crisis. For the Muslim community, the Prophet Muhammad peace and blessings of Allah be upon him is a role model in all aspects of life, because his teachings have presented everything that mankind needs, both in matters of the hereafter and in the world. Through qualitative research, the researcher tried to reveal the guidance of the Prophet Muhammad peace and blessings of Allah be upon himin facing and resolving the threat of economic crisis. By collecting the data from the Qur’an, hadith, and scholars' statements, the researcher tries to get a clear picture of these guidance.Hopefully, these guidance can be applied by the Muslim community in facing the threat of the economic crisis that is currently haunting the international community. From this research, it was revealed that the main cause of the economic crisis was human behavior that deviated from the guidance of Sharia.Therefore, faith in Allah the Exalted, the Lord of the universe, is a solid foundation as well as a source of inspiration for Muslims in facing all the dynamics of life, including the threat of economic crises. As it is revealed that the Islamic Sharia has arrangedcomplete solutions to solve the threat of the economic crisis.